Environmental Audit of Legal Conformity in the Industry: a theory study about Brazilian legislation´s parameter - Dutra, Leonardo Masseli (Revista Ciências Exatas, 2008)
This study presents a research about Legal Conformity Audits applicable at industrial activities. All federal, state and city’s Brazilian regulations regarding to Environmental Audit, applicable to industries facilities have been studied and analyzed. Besides the advantage regarding to prevention, the Legal Conformity Audit provides to industrial activities a good safety margin related to environmental risks, since the law is no more than a standardization of power and responsibility. The proposal is to discuss the theme by analyzing several items applicable to industrial activities on the Brazilian regulation, comparing them, to find out, between those concepts, which one could be used by the facilities, aiming to improve the company’s environmental management.